Impact of trauma workshop on knowledge, attitude and practice conducted on undergraduate MBBS students - Kulkarni Uma1, Dongare Harshad2 ,Dongare Dhanashree2 (Perspectives In Medical Research, 2020)
In India the organized trauma care services are restricted only to tertiary care centres and golden hour trauma care is often delayed. We decided to create awareness among the MBBS students by teaching basic trauma management skills since they are the first responders to a trauma victim brought to any hospital setup. This would help improve primary trauma care. Aim: To assess the improvement in knowledge, attitude and practice after primary trauma care workshop in MBBS students Methods and Material: A one day primary trauma care workshop was conducted in our institute for two consecutive years during the annual academic undergraduate conference 2018 and 2019 respectively. The MBBS students enrolled were given a questionnaire to solve before and after the workshop. They received a lecture on triage and hands-on practice on Primary survey, log roll & cervical spine stabilization, Airway management, Intravenous fluids & shock management and Basic life support. Statistical analysis: The pre and post workshop questionnaires were statistically analyzed by paired t-test using software version SPSS 20.0 and a P value of < 0.05 was considered statistically significant. Results: Pre workshop 9.9% and 10.5% of the students had above average total score in 2018 and 2019 respectively which increased to 67.6% and 78.5% post workshop. The mean Knowledge, Attitude and Practice scores also improved individually. Conclusion: We should include such workshops in the undergraduate curriculum, it would improve primary trauma care and will reduce trauma related morbidity and mortality